2015
DOI: 10.1080/07391102.2015.1100139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the free and inhibitor-bound cruzain systems in aqueous solvent: insights on the inhibition mechanism in acidic pH

Abstract: The major cysteine protease of Trypanosoma cruzi, cruzain (CRZ), has been described as a therapeutic target for Chagas' disease, which affects millions of people worldwide. Thus, a series of CRZ inhibitors has been studied, including a new competitive inhibitor, Nequimed176 (NEQ176). Nevertheless, the structural and dynamic basis for CRZ inhibition remains unclear. Hoping to contribute to this ever-growing understanding of timescale dynamics in the CRZ inhibition mechanism, we have performed the first study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
1
3
0
2
Order By: Relevance
“…But PCA has successfully captured a clear difference in the tendency of conformational space from this limited data set . These inherent characteristics shall be reflected in a much longer and biologically relevant time scale and this hypothesis is in agreement with that fact that in vitro studies on this protein–ligand interaction have already reported the possible conformational switching. , …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…But PCA has successfully captured a clear difference in the tendency of conformational space from this limited data set . These inherent characteristics shall be reflected in a much longer and biologically relevant time scale and this hypothesis is in agreement with that fact that in vitro studies on this protein–ligand interaction have already reported the possible conformational switching. , …”
Section: Resultssupporting
confidence: 83%
“…39 These inherent characteristics shall be reflected in a much longer and biologically relevant time scale and this hypothesis is in agreement with that fact that in vitro studies on this protein−ligand interaction have already reported the possible conformational switching. 15,40 Accessible Conformational Space. It was observed that first four principal component (PC) modes comprised ∼65− 80% (Figure S5) of the overall dynamics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As successfully shown by previous studies [ 26 , 27 , 28 , 29 , 30 , 31 ], MD simulations are an excellent technique to improve molecular docking results. Here, as described in the Materials and Methods section, five random replicas of 2 ns each were performed by using the Q program [ 32 ] version 6.0 [ 33 ] to provide ensembles for an improved binding process of 1,2,3-triazole-based KA into TYR.…”
Section: Resultsmentioning
confidence: 84%
“…Durrant et al (2010) used sequence analysis and MD simulations to explore additional binding sites in cruzain. Hoelz et al (2016) studied free and liganded cruzain dynamics at acidic pH, which corresponds to its environment in the cell. Very recently, Cianni et al (2018) also used MD simulations to study the binding mode of reversible covalent inhibitors to the less frequently studied specific subsite S3 of cruzain.…”
Section: Cysteine Proteasesmentioning
confidence: 99%